(untitled) (ModaPalavra e-periódico, 2013)
This paper is the result of research that describes the development of a fashion collection from a compiled design methodologies. This compiled attempted to combine steps taken in product design with steps used in the development of fashion collections. Finally, the article reflects on the general effects of the research, and, more particularly, on the approach taken between the universe of product design methodology, and the project universe of developing fashion collection